Surface tension and density of copper–Zirconium alloys in contact with fluoride refractories - Krasovskyy, V. P.; Naidich, Y. V.; Krasovskaya, N. A. (Journal of materials science, 2005)
The surface tension and density of copper–zirconium alloys were measured over a wide range of zirconium concentration (from 7.182 to 74.0 at.%) at temperatures between 1000 and 1250∘C by the “large drop” method in cups made on calcium fluoride. The surface tension and density polytherms are straight lines with negative temperature coefficients. The excess volume of mixing is negative, the maximum decrease in volume, observed for a 47.0 at.% Zr alloy, being 3.4%